Time-of-day effects of exposure to solar radiation on thermoregulation during outdoor exercise in the heat. (21st October 2017) - Otani, Hidenori; Goto, Takayuki; Goto, Heita; Shirato, Minayuki
ABSTRACT: High solar radiation has been recognised as a contributing factor to exertional heat-related illness in individuals exercising outdoors in the heat. Although solar radiation intensity has been known to have similar time-of-day variation as body temperature, the relationship between fluctuations in solar radiation associated with diurnal change in the angle of sunlight and thermoregulatory responses in individuals exercising outdoors in a hot environment remains largely unknown. The present study therefore investigated the time-of-day effects of variations in solar radiation associated with changing solar elevation angle on thermoregulatory responses during moderate-intensity outdoor exercise in the heat of summer. Eight healthy, high school baseball players, heat-acclimatised male volunteers completed a 3-h outdoor baseball trainings under the clear sky in the heat. The trainings were commenced at 0900 h in AM trial and at 1600 h in PM trial each on a separate day. Solar radiation and solar elevation angle during exercise continued to increase in AM (672–1107 W/m 2 and 44–69°) and decrease in PM (717–0 W/m 2 and 34–0°) and were higher on AM than on PM (both P  < 0.001). Although ambient temperature (AM 32–36°C, PM 36–30°C) and wet-bulb globe temperature (AM 31–33°C, PM 34–27°C) also continued to increase in AM and decrease in PM, there were no differences between trials in these (both P  > 0.05). Tympanic temperature measured by an infrared tympanic thermometer and mean skin temperature were higher in AM than PM at 120 and 180 min ( P  < 0.05). Skin temperature was higher in AM than PM at the upper arm and thigh at 120 min ( P  < 0.05) and at the calf at 120 and 180 min (both P  < 0.05). Body heat gain from the sun was greater during exercise in AM than PM ( P  < 0.0001), at 0–60 min in PM than AM ( P  < 0.0001) and at 120–180 min in AM than PM ( P  < 0.0001). Dry heat loss during exercise was greater at 0–60 min ( P  < 0.0001), and lower at 60–120 min ( P  < 0.05) and 120–180 min ( P  < 0.0001) in AM than PM. Evaporative heat loss during exercise was greater in PM than AM at 120–180 min ( P  < 0.0001). Total (dry + evaporation) heat loss at the skin was greater during exercise in PM than AM ( P  < 0.0001), at 0–60 min in AM than PM ( P  < 0.0001) and at 60–120 and 120–180 min in PM than AM ( P  < 0.05 and 0.0001). Heart rate at 120–150 min was also higher in AM than PM ( P  < 0.05). Neither perceived thermal sensation nor rating of perceived exertion was different between trials (both P  > 0.05). The current study demonstrates a greater thermoregulatory strain in the morning than in the afternoon resulting from a higher body temperature and heart rate in relation to an increase in environmental heat stress with rising solar radiation and solar elevation angle during moderate-intensity outdoor exercise in the heat. This response is associated with a lesser net heat loss at the skin and a greater body heat gain from the sun in the morning compared with the afternoon.